The electromagnetic cause of gravity (International Journal of Scientific Research and Management (IJSRM), 2023)
Under the condition of the expansion of the universe and all masses with their atoms and charges in it, the electromagnetic cause of the gravitational force is determined with the help of the Lorentz force. The gravitational force, which could be founded here electromagnetically, is indentical with the mechanical gravitational force of Newton, which is cofirmed experimentally many times and is correct, but still unfounded.